Actually Getting Some Satisfaction on the Job: Need–Supply Fit of Fundamental Motives at Work - Dörendahl, Jan; Niepel, Christoph; Greiff, Samuel (Frontiers in Psychology, 2020)
The fit between employees’ needs and the opportunity to satisfy them in the workplace is an important predictor of job satisfaction. To make full use of this concept in career development, a fine-grained assessment of needs is necessary to allow for a straightforward interpretation. Fundamental motives provide a theoretically meaningful, self-contained framework of 16 fine-grained explicit motives, including, for instance, Social Acceptance, Curiosity, and Autonomy. Based on a series of response surface analyses in a German online sample of 723 working people, we examined the impact on job satisfaction of three different combinations of fundamental motives and their supply: exact congruence, an excess in the supply, and a shortage in the supply. For an excess in the supply, the results suggest that job satisfaction was highest for Social Acceptance, Status, Autonomy, Sex, and Retention. For a congruence of high motive levels and high supply levels, the levels of job satisfaction were highest for Curiosity, Idealism, and Social Participation. Concerning a shortage in the supply, low levels of job satisfaction were observed for Social Acceptance, Status, Sex, Retention, Curiosity, and Idealism. The results can be useful in coaching and career developments to provide information about potential sources of low job satisfaction and provide guidance to clients on how to enhance their job satisfaction.